Proportion of Home and Leisure Accidents in mainland Portugal, in 2019. (30th September 2020) - Alves, T; Rodrigues, E; Neto, M; Mexia, R; Matias-Dias, C
Abstract: Unintentional injuries are recognized by the World Health Organization and the European Union as a preventable public health problem contributing to mortality and morbidity burden and expression in the emergency department (ED). According to EuroSafe injury is the fourth most common cause of death within the EU, being the leading cause of death in the youngest. Whereas injury related fatalities is only a part of the problem and more patients require hospital treatment it is essential measure the size of the injury problem and characteristics of these non-fatal injuries. Information from Injury Data-Base reveals that the majority of injury related ED attendances and hospital admissions result from accidents occur in home and during leisure times. So, the aim of this study it was to know the proportion of Home and Leisure Accidents (HLA) which needed attendance in the emergency rooms of the Hospitals National Health, in Portugal Mailand, in 2019. For the analysis were considered the total number of NHS health entities that have an ED, SONHO information system and National injury surveillance system - EVITA System. Based on hospital emergency records in 2019, was obtained the total number of victims by HLA who needed assistance in this health services. In 2019, there were 526 786 ED attendances due to HLA, so about 11, 3% of hospital ED attendances in mainland Portugal were caused by HLA. Globally, it was observed a proportion of HLA with admission in ED higher in males (12, 9%) than females (10, 1%). Disaggregating the data by age group, it was possible to observe a preponderance of males in victims aged less than or equal to 54 years. On the other hand, females showed a higher proportion in individuals aged 55 and over. Additionally, victims aged 75 and over had the highest proportion of hospital admissions by HLA, both in females (15, 5%) and males (13, 1%). This study represented a relevant advance contributing to the revelation of the dimension of this problem in Portugal. Key messages: The National Injury Surveillance System provides information that allows to know the dimension of this health problem in mainland Portugal. HLA represents 11, 3 % of the total hospital ED attendances. HLA are the predominant cause of injury related ED attendances. Males and females have a different proportions of injury. Males aged 54 years and over have higher proportion of HLA than females.